Isolation and screening of cellulolytic bacteria from soil and optimization of cellulase production - Shilpa Lokhande; Pethe AS (International Journal of Life Sciences, 2017)
The present investigation was undertaken to isolate and Screen the Cellulase Producing bacteria. Microbial cultures were isolated from the soil sample collected from different villages of saline belt of Akola and Buldhana District, Maharashtra India. A Total of 146 isolates were isolated and identified based on Morphology and Biochemical characterization. Among all isolated organisms 37 bacterial species were isolated, the one cellulolytic bacterial isolate shows maximum enzyme activity, and identified as Bacillus thuringiensis. The best conditions like pH, carbon source, temperature and incubation period were also observed for cellulase producing organisms. Carboxy methyl cellulose [1.0% (w/v)] were found to be the best carbon source for the production of cellulase and Optimum temperature and pH of the medium for the cellulase were 40°C and 7, whereas it shows maximum enzyme activity after third day of incubation period.